The Influence Of Boarding School Environment And Social Media On The Development Of Pancasila Student Profiles: The Mediation Role Of Social Contribution And Self-Resistance - Fransiska Romana Wuriningsih; Nerita Setiyaningtiyas (UNIVERSITAS PAKUAN, 2024)
Study This aiming For analyze influence boarding school environment and social media use to development profile Pancasila students in students, with contributions social and resilience self as variable mediation. Profile Pancasila students are initiative the Indonesian government to to form generation that has character strong, have integrity, and be able apply Pancasila values in life everyday. The research method used is approach quantitative with design correlational survey, which involves students in the boarding school environment as respondents. Data collected through questionnaire that includes aspect boarding school environment, use of social media, contribution social, resilience self, and characteristics Pancasila Students. Data analysis was carried out using the technique regression multiple and analysis track For test influence direct and also No direct between variable independent, mediation, and dependent. Research results This expected give description about to what extent the boarding school environment and social media play a role in development Pancasila values in students, as well as role important contribution social and resilience self as factor mediation. Findings This expected can become reference for institution education in optimize environment learning and use of social media For to form character student according to profile Pancasila Students.